2017
DOI: 10.1155/2017/8634540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transplantation of Bone Marrow Derived Mesenchymal Stem Cells and Platelets Rich Plasma on Experimental Model of Radiation Induced Oral Mucosal Injury in Albino Rats

Abstract: Normal tissue damage following radiotherapy is still a major problem in cancer treatment. Therefore, the current work aimed at exploring the possible role of systemically injected bone marrow derived mesenchymal stem cells (BM-MSCs) and/or locally injected platelet rich plasma (PRP) in ameliorating the side effects of ionizing radiation on the rat's tongue. Twelve rats served as control group (N) and 48 rats received a single radiation dose of 13 Gy to the head and neck region; then, they were equally divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 43 publications
5
34
0
Order By: Relevance
“…In the current study, PRP treatment were able to restore the normal architecture of tongue papillae after ASP treatment. The improved histological and SEM features detected here were in agreement with the results of a recent study by Elsaadany et al (34) who concluded the positive effects of PRP treatment in preventing or minimizing the epithelial atrophy of the dorsal surface of the tongue after radiotherapy. The positive effect of PRP observed here could be explained in the light of many previous studies that confirmed the effectiveness of growth factors derived platelets to enhance cell proliferation, differentiation, chemotaxis, angiogenesis, and extracellular matrix synthesis involved in the healing of mucositis after irradiation (35,36) .…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, PRP treatment were able to restore the normal architecture of tongue papillae after ASP treatment. The improved histological and SEM features detected here were in agreement with the results of a recent study by Elsaadany et al (34) who concluded the positive effects of PRP treatment in preventing or minimizing the epithelial atrophy of the dorsal surface of the tongue after radiotherapy. The positive effect of PRP observed here could be explained in the light of many previous studies that confirmed the effectiveness of growth factors derived platelets to enhance cell proliferation, differentiation, chemotaxis, angiogenesis, and extracellular matrix synthesis involved in the healing of mucositis after irradiation (35,36) .…”
Section: Discussionsupporting
confidence: 92%
“…This effect on the connective tissue coincides with El-Saadany et al, 2017 who presented radiationinduced mucositis of rat tongue. (51) However, the detected immunopositive reaction in our results matches the results of Lee et al, 2005 who detected caspase expression in the muscles of the irradiated rats. (52) The present study could give a primary assessment of the dose dependent radiation effects on the lingual internal structures, however, more effort might be needed to evaluate the reversibility of these effects and the possible ways for protection of radiation-induced changes.…”
Section: Discussionsupporting
confidence: 92%
“…BMCs promote tissue renewing and repairing through synergistic down regulation of proinflammatory cytokines and increased production of soluble factors with antioxidant property. Furthermore, BMCs enhance cell proliferation or inhibit the epithelial cell apoptosis, or by a combination of both [41]. A third mechanism may be transdifferentiation of BMCs after they are reprogrammed by the microenvironment in the injured colon.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the fundamental role of stem cell microenvironment in inhibiting carcinogenesis is by providing signals to suppress proliferation and to enhance differentiation. Additionally, it was suggested that engrafted MSCs also differentiated into colonic interstitial lineage cells and secreted vascular endothelial growth factor (VEGF) and transforming growth factor beta-1 (TGF-β1) those playing an important role in healing of injured colonic mucosa [41]. Supporting this observation, BMCs allograft to sites of Kaposi’s sarcoma potently inhibits tumor growth by down-regulating protein kinase B (AKT) activity in tumor cells [44].…”
Section: Discussionmentioning
confidence: 99%